Matematyka
ewelcia16
2017-12-28 19:57:49
Oblicz wartość wyrażeń. -28+12*(-0,5)^2-6*(-1/2)^3= , -(-1/2)^3+(-0,4)^3:(1 i1/5)^2*2i13/16= Reszta w załączniku
Odpowiedź
johnybarca
2017-12-29 01:30:43

a) [latex]28+12* frac{1}{4} -6*(-frac{1}{8})= -28+3+3/4=-24 frac{1}{4} [/latex] b)  [latex] frac{1}{8} - frac{8}{125} * frac{25}{36} * frac{45}{16} = frac{1}{8} - frac{1}{8} = 0[/latex] c)  [latex] frac{1}{8} - frac{8}{125} * frac{25}{36} * frac{45}{16} - ( - frac{9}{16} + frac{25}{16} ) -4* frac{1}{16} = -1- frac{1}{4} = - frac{3}{4} [/latex] d)  [latex]130 - ( 36* frac{4}{9} - frac{9}{8} + frac{1}{8} ) * frac{7}{30} =[/latex]  [latex]130 - (16 -1)* frac{7}{30} = 130-15* frac{7}{30} = 130 - frac{7}{2} = 126 frac{1}{2} [/latex]

Dodaj swoją odpowiedź